2009
DOI: 10.1097/hjh.0b013e32832401ff
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy versus chronic kidney disease as predictors of cardiovascular events in hypertension: a Greek 6-year-follow-up study

Abstract: In hypertensive patients free of cardiovascular disease, CKD and LVH are both independent prognosticators of the composite end point of all-cause death and cardiovascular morbidity, whereas LVH but not CKD is a major predictor for stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 46 publications
1
36
0
5
Order By: Relevance
“…Along these lines, we recently showed in hypertensives that the presence of both LVH and chronic kidney disease was associated with a 2.5-fold increase in coronary events, a 4-fold increase in stroke, whereas the presence of LVH alone was associated with a 2.5-fold higher risk for stroke [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, we recently showed in hypertensives that the presence of both LVH and chronic kidney disease was associated with a 2.5-fold increase in coronary events, a 4-fold increase in stroke, whereas the presence of LVH alone was associated with a 2.5-fold higher risk for stroke [38]. …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Among these manifestations of cardiac damage, particular attention has been devoted to LVH because this phenotype has been reported to be a powerful, independent predictor of cardiovascular (CV) events and all-cause mortality either in the general population or in hypertensive cohorts. 6,7 Although the pathogenesis of hypertensive LVH is not fully understood, a consistent body of evidence indicates that the severity of pressure overload, as better reflected by out-of-office than by in-office blood pressure (BP) levels, in combination with nonhemodynamic variables, including genetic, ethnic, and humoral factors, plays a pivotal role in its development. 8,9 Nonetheless, numerous reports have also shown that circadian variations in BP correlate to LVH independently of 24-hour ambulatory BP monitoring (ABPM) values.…”
mentioning
confidence: 99%
“…Left ventricular (LV) hypertrophy (LVH), either detected by electrocardiography or echocardiography, has been shown to be an independent predictor of nonfatal and fatal cardiovascular (CV) events as well as all-cause death in a variety of clinical settings including general population-based samples 1,2 and selected cohorts of hypertensive, [3][4][5] coronary artery disease, 6 chronic kidney disease, 7 and heart failure patients. 8 Thus, the accurate and cost-effective identification of LVH represents a clinical priority for stratifying individual CV risk.…”
mentioning
confidence: 99%